CORPORATE GOVERNANCE MANAGEMENT TOWARDS COMPANIES INCLUDING IN LQ45 INDEX - Dwi Fuji Wahyuni; Masyhuri Hamidi (Program Pascasarjana STIE Amkop Makassar, 2020)
This research investigates the effects of managerial ownership, intitutional ownership and independent board of commissioners on earnings management either simultanleously or partially. Population of this research are companies listed on Indonesian Stock Exchange that registered in LQ45 index from 2014-2018. The type of this research is descriptive study and using secondary data from the financial reports. This reseach uses multiple linier regression technique, using firm size as a control variable. where the results of this research show that simultaneously managerial ownership, institutional ownership, independent board of commissioners, and firm size have significant effect to earnings management. Partially, intitutional ownership have no significant effect to earnings management, managerial ownership have no significant effect to earnings management and independent board of commissioners have no significant effect to earnings management. Keywords: institutional ownership, managerial ownership,independent board of commissioners